Analisis Efektivitas Model Epic Pada Khalayak Kanal Youtube Abroad in Japan - Dermawan, Rizky Okta; Aryapranata, Ariawan; AL Rasyid, Yuliansyah (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan DigitalDO - 10.30647/jpbd.v2i2.2118, 2026)
This study aims to analyze the effectiveness of Visual Storytelling on the Abroad in Japan YouTube channel in building Destination Branding among Generation Z and Millennials in Indonesia. The study employed a descriptive quantitative approach using a survey method, with respondents selected through purposive sampling. The research instrument was developed based on the EPIC Model, which consists of four dimensions: Empathy, Persuasion, Impact, and Communication . The collected data were analyzed using descriptive statistics and cross-tabulation based on respondents’ demographic characteristics, including occupation, gender, and YouTube consumption intensity. The findings indicate that Visual Storytelling on the Abroad in Japan channel is generally effective in supporting Destination Branding . The Communication dimension emerged as the strongest aspect, as transparency, objectivity, and clarity of information enhance the credibility of tourism messages. The Persuasion dimension demonstrates the content’s ability to encourage audiences to consider Japan as a travel destination, while Impact strengthens destination recall through cinematography and visual editing quality. The Empathy dimension requires further improvement due to a gap in emotional relatability associated with perceptions of travel costs. Keywords: visual storytelling, destination branding, EPIC Model, YouTube